Bermain Sambil Belajar Berwirausaha Mengasah Keterampilan dan Kemampuan Entrepreneurship Melalui Craft Day - Sukma, Septi Ambar Indraningtia; Widodo, Slamet; Lembang Jaya, Muhamad; Fitriani, Lia Firdia; Ayu Agustin, Wilujeng; Noratama, Gilang; Nur Azizah, Firda Nikmah (Jumat Ekonomi: Jurnal Pengabdian Masyarakat, 2024)
ABSTRACT Character formation in the world of education can start from early childhood and elementary school education according to Mulyani, 2012 in (Badawi, 2023). Early childhood education must introduce entrepreneurial values ​​and character (Saaadah & Nurjaman, 2023). Efforts to foster entrepreneurial character can be done through entrepreneurial activities from an early age, and this can be applied in Craft Day activities which can be an opportunity for students to be creative in producing work and selling their own work. The aim of this program is to introduce the concept of entrepreneurship to elementary school and Madrasah Ibtidaiyah students. To provide an understanding of the basic concepts of entrepreneurship related to planning, marketing and sales in a simple way to elementary school and Ibtidaiyah Madrasah students. The program "Playing While Learning to be Entrepreneurial, Sharpening Entrepreneurship Skills and Abilities through Craft Day" produces important conclusions in several aspects. First, this program provides an in-depth understanding of the basics of entrepreneurship for Kedungbogo . Keywords: Craft Day, Entrepreneurship, Elementary School And Ibtidaiyah Madrasah Students.